The Development of Online Lessons for Promoting Piano Playing Skills for Non-piano Playing Background Students - Guobin, Zhou; Suttachitt, Narutt; Charoensloong, Thitinun; Daoruang, Krisada (Journal of Ecohumanism, 2025)
This study explores the process of developing online courses to improve the piano-playing skills of students with no piano-playing experience, designs and develops practical online piano courses for students and evaluates the effectiveness and practicality of the developed online courses in enhancing students' piano skills. This is research and development approach collecting data from 35 students. This study uses four tools: course plans and expert validation forms, interview and questionnaire forms, and pretest and post-test evaluations of piano performance skills. Data were analyzed by statistical and content analysis. The findings reveal that online piano lesson assessment step involves expert validation and trials to evaluate the online piano lesson design outcomes. The expert validation of the online piano lesson design and tools, including lesson plans, learning implementation observation sheets, and student response sheets. The expert assessment of the online piano lesson design encompasses the evaluation of several components, such as the correctness of the information provided on the rationale for developing online piano lessons, the theoretical foundations underlying the lessons, and the different learning components included (including learning steps, social systems, reaction principles, and support systems). The online piano lessons in the study were convenient, with an average learning implementation score of 4.20 out of a possible score of 5. Beginners have significantly improved their piano playing skills in various dimensions. These improvements were reflected in the mastery of basic playing skills and the flexible use of complex rhythms and chords. The course design emphasizes training in two-handed coordination, touch techniques, and rhythm. The successful development of the course has provided a flexible and efficient learning path for students with no prior piano playing background and has demonstrated the significant educational value and prospects for the promotion of online piano teaching in developing the skills of beginning piano students